Evaluation of a vitamin D screening and treatment protocol using a seasonal calculator in athletes - Hollabaugh, W. L.; Meirick, P. J.; Matarazzo, C. P.; Burston, A. M.; Camery, M. E.; Ferrill-Moseley, K. A.; Bley, J. A.; Pennings, J. S.; Fitch, R. W.; Tanner, S. B.; Karpinos, A. R. (Current Sports Medicine Reports, 2022)
Vitamin D is important in musculoskeletal health, and low serum vitamin D concentration is common in athletes. This study implemented a vitamin D screening and supplementation protocol in a cohort of National Collegiate Athletic Association Division I athletes using summer 25-hydroxyvitamin D concentration and a seasonal variation calculator to achieve sufficient vitamin D concentration year-round. After implementation of the Vitamin D Protocol, there was a nonsignificant difference in athletes with sufficient winter vitamin D concentrations (72.6%) compared with summer vitamin D concentrations (66.1%) (P = 0.40). The Seasonal Variation Calculator predicted winter vitamin D concentrations (8 ± 18 ng/mL) higher than actual winter vitamin D concentrations (P < 0.01). While most athletes (78%) believed vitamin D was important for athletic performance, athlete compliance to the Vitamin D Protocol was inconsistent. In the future, adjustment of vitamin D screening and supplementation protocols may help athletes achieve sufficient vitamin D status year-round.